Effect of ultra-processed foods consumption on glycemic control and gestational weight gain in pregnant with pregestational diabetes mellitus using carbohydrate counting - Silva, Carolina F. M.; Saunders, Claudia; Peres, Wilza; Folino, Bárbara; Kamel, Taiana; dos Santos, Mayara Silva; Padilha, Patrícia (PeerJ, 2021)
Aims The aims were to evaluate the consumption of ultra-processed foods by pregnant women with pre-existing diabetes mellitus (DM) using the carbohydrate counting method, in addition to investigating the association with total gestational weight gain and glycemic control. Methods A cohort study of adult Brazilian pregnant women with pre-existing DM. Dietary intake was evaluated adopting the NOVA classification to identify the reported consumption of ultra-processed foods. Weight was measured at all consultations and laboratory tests were evaluated at each gestational trimester. Multivariate linear regression was used in the analysis. Results Pregnant women (n = 42) presented mean total gestational weight gain of 12.02 ± 4.8 kg, 65.8% of them with inadequate weight gain. Daily consumption of ultra-processed foods was 272.37 ± 170.55 kcal. The increase of every 1 kcal in the calorie intake from ultra-processed foods in the third trimester increased glycated hemoglobin by 0.007% (β = 0.007, p = 0.025), raised 1-h postprandial glucose by 0.14 mg/dL (β = 0.143, p = 0.011), and added 0.11 kg to total gestational weight gain (β = 0.11, p = 0.006). Conclusion Ultra-processed food consumption influenced glycemic control and total gestational weight gain in pregnant women with DM.
Keywords: Maternal nutrition; Prenatal care; Diabetes mellitus; Blood glucose; Weight gain